Robust multi-user detection based on hybrid grey wolf optimization - Ji, Yuanfa; Fan, Z .; Sun, X.; Wang, S.; Yan, S.; Wu, S.; Fu, Q.; Kamarul Hawari, Ghazali (Springer Nature Switzerland, 2020)
The search for an effective nature-inspired optimization technique has certainly continued for decades. In this paper, a novel hybrid Grey wolf optimization and differential evolution algorithm robust multi-user detection algorithm is proposed to overcome the problem of high bit error rate (BER) in multi-user detection under impulse noise environment. The simulation results show that the iteration times of the multi-user detector based on the proposed algorithm is less than that of genetic algorithm, differential evolution algorithm and Grey wolf optimization algorithm, and has the lower BER.